Prokonkurencyjne zmiany w polityce pomocy państwowej w Unii Europejskiej - Kąkol, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article concerns the most controversial area of the EU competition policy i.e. formal acceptance of state aid on the basis of some exemptions from the general rule prohibiting its granting. The signatories of the EEC Treaty created a lot of possibilities for member states to support their enterprises, and there are many examples when state intervention infringed the principle of free competition in the common market, delayed structural reforms as well as the process and effects of market liberalization. The most detrimental effect to the common market had state aid in the 70s, when member states in the circumstances of oil crisis and protracted economic downturn were extending the level of aid for own enterprises in order to strengthen their competitiveness in relation to the third countries but also in the common market. The Commission's policy turned out to be totally ineffective these days. The change of the Commission's attitude and the new approach to the matter of state intervention was caused by the Single Market Project 1992, realization of which started in the mid-80s. Creation of the internal market forced member states to reduce the level of state aid and to redirect it at less detrimental kinds of aid like horizontal aid (e.g. aid supporting research and development, the protection of environment, small and medium enterprises, training of less developed regions). But a visible limitation of state aid levels have been observed no sooner than since the mid-908, and its redirection to horizontal objectives only since the end of the 90s. Nowadays we are in the course of reform of the EU state aid policy. The reform process and its assumptions are based on the provisions of the Lisbon Strategy from March 2000. All the introduced changes serve to realize effectiveness goals. The author presents the development of the EU state aid policy and makes an attempt to evaluate its impact on competition in the common market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 198-212